Characterization of the geriatric patient with thyroid nodules - Jessica González Manreza; Gloría María Monné Rodríguez; Carlos Gaspar de Zayas Galván; Ángela Ramírez Torres; Erifran Hidalgo Garcés (Medisur)
Foundation: thyroid gland diseases are common in older adults and often go unnoticed. Objective: to characterize clinically and ultrasonographically geriatric patients with thyroid nodule. Methods: a cross-sectional descriptive observational study was carried out in the Martín Chang Puga Teaching General Hospital geriatrics service in Camagüey province, from 2019 to 2022. 48 elderly were the universe made up who attended in the service, and were diagnosed with nodular thyroid disease. The data was obtained from the patients' medical records, the age groups; sex, skin color, clinical manifestations, and ultrasound diagnosis were the analyzed variables. Results: the most affected age group was between 60 and 69 years old, with a predominance of females and white skin color. Asthenia prevailed within the clinical manifestations. In the ultrasound diagnosis, level I prevailed, according to the Thyroid Imaging Reporting and Data System. Conclusions: the high prevalence of thyroid diseases, especially in the elderly, makes it necessary to perform a screening for ultrasound diagnosis, as it is a beneficial, reliable and low-cost diagnostic test in Primary Health Care.